"How Can One Be a Romanian?": Modern Romanian Culture and the West - Călinescu, Matei (Southeastern Europe, 1983)
""How Can One Be a Romanian?": Modern Romanian Culture and the West" published on 01 Jan 1983 by Brill | Schöningh.